2020
DOI: 10.3389/fpsyg.2020.560064
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Sequence Learning in Attention Deficit Hyperactivity Disorder: A Meta-Analysis

Abstract: Previous literature proposes that the motor deficits in Attention Deficit Hyperactivity Disorder (ADHD) may be attributed to impairments of the procedural memory network, a long-term memory system involved in sensorimotor and cognitive skill development. A handful of studies have explored procedural sequence learning in ADHD, but findings have been inconsistent. A meta-analysis was conducted to begin to establish whether procedural sequence learning deficits exist in ADHD. The results of seven studies comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A meta-analysis investigating the presence of procedural sequence learning found that ADHD patients do not exhibit significant deficits and that procedural sequence learning appears to be intact in ADHD ( Sanjeevan et al, 2020 ). However, another study reported impaired results for procedural memory ( Butzbach et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis investigating the presence of procedural sequence learning found that ADHD patients do not exhibit significant deficits and that procedural sequence learning appears to be intact in ADHD ( Sanjeevan et al, 2020 ). However, another study reported impaired results for procedural memory ( Butzbach et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Visual episodic memory appears to be less affected compared to verbal episodic memory in patients with ADHD. However, impairments in verbal delayed recall and visual immediate and delayed recall have been observed, but recognition ability appears to be preserved irrespective of modality ( Aycicegi-Dinn et al, 2011 ; Callahan et al, 2017 ; Butzbach et al, 2019 ; Sanjeevan et al, 2020 ; Mohamed et al, 2021 ). Hence, the ability to store (transfer?)…”
Section: Methodsmentioning
confidence: 99%
“…In children with DCD, concurrent ADHD diagnosis was not an exclusion criterion (n = 19), as sequence-specific aspects seem preserved in the ADHD population (Sanjeevan et al, 2020;Takács et al, 2017). Associated symptoms might have a deleterious effect on the general aspects of the task (i.e., RTs and accuracy; Karatekin et al, 2009;Staels & Van den Broeck, 2017;Takács et al, 2017) and were controlled by converting RTs into normalized RTs.…”
Section: Methodsmentioning
confidence: 99%